Towards a dirty theory of narrative ethics: Prolegomenon on media, sport and commodity value - Wenner, Lawrence A (International Journal of Media & Cultural Politics, 2007)
Using sport as a lens to illuminate a path for broader cultural analysis, this essay argues for a three-pronged theoretical approach to the critique of commodity value in contemporary narratives. Three elements of an analytic strategy for the critique of commodity aesthetics are considered. First, the concept of communicative dirt posed by Leach (1976) and Hartley (1984) is considered in the service of creating commodity value from the cultural logic of sport. Second, the merits of a reader-oriented approach as used in literary criticism, reliant on understandings of Fish's (1976) notion of interpretive community and the variant ways that texts work to control reading, are considered as complementary to understanding the workings of communicative dirt. Third, the value of ethical criticism in providing an overarching frame for deconstructing the manufacture of commodity value, including strategies for using communicative dirt to construct readers and control the reading act, is assessed. A case study of a television commercial banned from the 2005 Super Bowl broadcast illustrates the tripartite approach. In conclusion, the study argues for the applicability of this dirty theory of narrative ethics to postmodern concerns with media in increasingly commodified contemporary culture.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9tYWNwLjMuMi4xMTFfMQ